KOMIK “KEMBALI KEPADA TUHAN” SEBUAH UPAYA PEMBELAJARAN MORAL SPIRITUAL BAGI REMAJA - Indiria Maharsi (DeKaVe, 2011)
Comic is one of the mass communication media that is encased and presented uniquely by combining texts and images. This combination may eventually create a plot which has a very broad effect because of the ability of this media to transform itself into various kinds of forms even for readers from various kinds of backgrounds. The application of the universal language of images makes the value of comics enhance into a kind of means to convey various kinds of messages, both simple and complex. With its flexible visual and verbal language comics can create an aesthetical visualization towards a current issue that is happening in the society. The comic Kembali Kepada Tuhan (Returning to God) is a comic title which is made based upon the social and spiritual conditions that occurs in Indonesia nowadays, about the habits of praying to other entities other than God. This comic is to make the youths nowadays not to follow such wrong example. Furthermore, it is hoped through this comic that the youths today understand the consequences if they follow that incorrect model. The reason of why this creation is targeted for today's youngsters is because of the nature of adolescents where they are vulnerable towards any bad external influences. Therefore, constant positive information and messages that deals with the moral and spiritual conditions during this period is necessary. This story is taken from many true stories that have ever happened in the society with the alteration of plots, settings, and characters; whereas, the idea is a combination from the visual reality and the enigma. The visual realities are to describe the human characters in the story. Meanwhile, the supernatural beings are derived enigmas that are caught from the spiritual realism. This comic gives a clear image for the targeted viewers if such habit is carried out. The comic itself uses the combination between digital coloring using Adobe Photoshop and manual drawing by using poster paint. Whereas, the images utilizes the realist style in order to emphasizes the reality aspect, an aspect that cannot beobtained using the cartoon style.Keyword : comics, adolescent, visualization